An improved outer bound for multiterminal source coding - Wagner, A.B.; Anantharam, V. (IEEE transactions on information theory, 2008)
We prove a new outer bound on the rate-distortion region for the multiterminal source-coding problem. This bound subsumes the best outer bound in the literature and improves upon it strictly in some cases. The improved bound enables us to obtain a new, conclusive result for the binary erasure version of the "CEO problem." The bound recovers many of the converse results that have been established for special cases of the problem, including the recent one for the Gaussian two-encoder problem.